2023
DOI: 10.1126/sciadv.adf4608
|View full text |Cite
|
Sign up to set email alerts
|

Six-month effective treatment of corneal graft rejection

Abstract: Topical corticosteroid eye drop is the mainstay for preventing and treating corneal graft rejection. While the frequent topical corticosteroid use is associated with risk of intraocular pressure (IOP) elevation and poor patient compliance that leads to graft failure and the requirement for a repeated, high-risk corneal transplantation. Here, we developed dexamethasone sodium phosphate (DSP)–loaded dicarboxyl-terminated poly(lactic acid) nanoparticle (PLA DSP-NP) formulations with relatively high drug loading (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Previously, we developed dexamethasone sodium phosphate (DSP)-loaded PLA-2COOH nanoparticle (PLA DSP-NP) that provided 6 month DSP release in rat eyes following a single subconjunctival (SCT) injection. 19 Here, we demonstrated that a single dosing of PLA DSP-NP, alone, prevented rat HR graft rejection for 6 months. We further engineered an axitinib-loaded nanowafer (Axi NW) for topical delivery of the TKI Axi.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Previously, we developed dexamethasone sodium phosphate (DSP)-loaded PLA-2COOH nanoparticle (PLA DSP-NP) that provided 6 month DSP release in rat eyes following a single subconjunctival (SCT) injection. 19 Here, we demonstrated that a single dosing of PLA DSP-NP, alone, prevented rat HR graft rejection for 6 months. We further engineered an axitinib-loaded nanowafer (Axi NW) for topical delivery of the TKI Axi.…”
mentioning
confidence: 74%
“…Previously, we developed a DSP- months. 19 To formulate PLA DSP-NP, the DSP−Zn complex was first prepared by mixing the two aqueous solutions, and the forming efficiency was more than 95% (Figure S1A). XRD analysis indicated that DSP displayed a classical crystalline structure with specific reflection in the range of 5−45°, whereas it switched to amorphous status after forming the DSP−Zn complex, indicating the coordination effects between DSP and zinc ions (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A single subconjunctival injection of PLA DSP nanoparticles effectively reversed early signs of corneal graft rejection and maintained the graft survival for at least 6 months in rats. [ 117 ] To further prolong the release of hydrophobic small molecules, PCL can be leveraged to form LAIs as it is more hydrophobic than PLGA and hence degrades at a slower rate. [ 118 ] Indeed, rapamycin and omidenapag isopropyl (DE‐117) were released from PCL for 16 and 24 weeks, respectively.…”
Section: Modifying Carrier Physicochemical Properties For Enhanced Oc...mentioning
confidence: 99%
“…[115,116] Meng et al formulated long-acting PLA-based microparticles for the sustained release of dexamethasone disodium phosphate (DSP) to prevent corneal graft failure. [117] They increased the encapsulation efficiency of DSP via the formation of an ionic bridge between the terminal carboxyl groups of their customized PLA and the phosphate groups from DSP using zinc. A single subconjunctival injection of PLA DSP nanoparticles effectively reversed early signs of corneal graft rejection and maintained the graft survival for at least 6 months in rats.…”
Section: Tuning Polymer Physicochemical Properties Prolongs Drug Phar...mentioning
confidence: 99%